2015
DOI: 10.1016/j.bbi.2014.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lipopolysaccharide administration impairs retrieval of context–object discrimination, but not spatial, memory: Evidence for selective disruption of specific hippocampus-dependent memory functions during acute neuroinflammation

Abstract: Neuroinflammation is implicated in impairments in neuronal function and cognition that arise with aging, trauma, and/or disease. Therefore, understanding the underlying basis of the effect of immune system activation on neural function could lead to therapies for treating cognitive decline. Although neuroinflammation is widely thought to preferentially impair hippocampus-dependent memory, data on the effects of cytokines on cognition are mixed. One possible explanation for these inconsistent results is that cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 80 publications
4
71
0
Order By: Relevance
“…Because of a high density of cytokine receptors [35], hippocampus as an important responsible area for consolidation of spatial memory and LTP induction could be vulnerable to neuro-inflammation [36]. It has been well documented that immune system stimuli such as LPS disturb hippocampusdependent learning processes including learning of spatial tasks and contextual consolidation [37]. LPS also attenuates spatial memory through the reduction of the number and the size of new neurons in dentate gyrus [38].…”
Section: Discussionmentioning
confidence: 99%
“…Because of a high density of cytokine receptors [35], hippocampus as an important responsible area for consolidation of spatial memory and LTP induction could be vulnerable to neuro-inflammation [36]. It has been well documented that immune system stimuli such as LPS disturb hippocampusdependent learning processes including learning of spatial tasks and contextual consolidation [37]. LPS also attenuates spatial memory through the reduction of the number and the size of new neurons in dentate gyrus [38].…”
Section: Discussionmentioning
confidence: 99%
“…Due to a high density cytokines receptors, hippocampus has been considered to be very vulnerable to inflammation 27 . Using animal models, it has been indicated that administration of cytokines or other immune system stimuli including LPS deteriorate hippocampus-dependent learning and memory process 24 . Recently, the brain tissues oxidative damage was considered to have an important role in deleterious effects of LPS on learning and memory 16 .…”
Section: Discussionmentioning
confidence: 99%
“…All these findings confirm the results of our study. During inflammation responses, microglia as the principle effectors of immune system in the brain, release pro-inflammatory cytokines which directly affects neuronal function including long-term potentiation, glutamate release and cell signaling pathways 24 . LPS has been shown that triggers the overproduction of pro-inflammatory cytokines such as TNF α , IL-1β , IL-6 13,25 .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, studies have elucidated the mechanism by which inflammation interferes with the acquisition and extinction of fear. Specifically, LPS administration disrupts cellular processes in the hippocampus critical for memory formation (Czerniawski et al, 2015), and increases in IL-6 (Burton and Johnson, 2012) and IL-1β (Gonzalez et al, 2013) interfere in this LPS-induced deficit in memory. Additionally, site-specific injections of both IL-6 (Hao et al, 2014) and TNFα (Jing et al, 2015) into the amygdala impair the acquisition and extinction of fear conditioning.…”
Section: Inflammation As a Common Underlying Mechanismmentioning
confidence: 99%